At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To show that quadrilateral KITE with vertices [tex]\( K (0, -2), I (1, 2), T (7, 5) \)[/tex], and [tex]\( E (4, -1) \)[/tex] is a kite, we need to use the distance formula to determine the lengths of the sides of KITE and show that it has two pairs of adjacent sides that are equal.
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Step 1: Calculate [tex]\( KI \)[/tex]:
[tex]\[ KI = \sqrt{(1 - 0)^2 + (2 - (-2))^2} \][/tex]
[tex]\[ KI = \sqrt{1 + 16} \][/tex]
[tex]\[ KI = \sqrt{17} \][/tex]
Step 2: Calculate [tex]\( KE \)[/tex]:
[tex]\[ KE = \sqrt{(4 - 0)^2 + (-1 - (-2))^2} \][/tex]
[tex]\[ KE = \sqrt{16 + 1} \][/tex]
[tex]\[ KE = \sqrt{17} \][/tex]
Step 3: Calculate [tex]\( IT \)[/tex]:
[tex]\[ IT = \sqrt{(7 - 1)^2 + (5 - 2)^2} \][/tex]
[tex]\[ IT = \sqrt{36 + 9} \][/tex]
[tex]\[ IT = \sqrt{45} \][/tex]
Step 4: Calculate [tex]\( ET \)[/tex]:
[tex]\[ ET = \sqrt{(7 - 4)^2 + (5 - (-1))^2} \][/tex]
[tex]\[ ET = \sqrt{9 + 36} \][/tex]
[tex]\[ ET = \sqrt{45} \][/tex]
We notice that:
[tex]\[ KI = KE = \sqrt{17} \][/tex]
[tex]\[ IT = ET = \sqrt{45} \][/tex]
Since KITE has two pairs of adjacent sides that are equal ([tex]\( KI = KE \)[/tex] and [tex]\( IT = ET \)[/tex]), we can conclude that KITE is a kite.
Therefore, fill in the drop-down menus as follows:
1. [tex]\( IT = \sqrt{45} \)[/tex]
2. [tex]\( ET = \sqrt{45} \)[/tex]
3. Therefore, KITE is a kite because it has two pairs of adjacent sides of equal length, [tex]\( KI = KE \)[/tex] and [tex]\( IT = ET \)[/tex].
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Step 1: Calculate [tex]\( KI \)[/tex]:
[tex]\[ KI = \sqrt{(1 - 0)^2 + (2 - (-2))^2} \][/tex]
[tex]\[ KI = \sqrt{1 + 16} \][/tex]
[tex]\[ KI = \sqrt{17} \][/tex]
Step 2: Calculate [tex]\( KE \)[/tex]:
[tex]\[ KE = \sqrt{(4 - 0)^2 + (-1 - (-2))^2} \][/tex]
[tex]\[ KE = \sqrt{16 + 1} \][/tex]
[tex]\[ KE = \sqrt{17} \][/tex]
Step 3: Calculate [tex]\( IT \)[/tex]:
[tex]\[ IT = \sqrt{(7 - 1)^2 + (5 - 2)^2} \][/tex]
[tex]\[ IT = \sqrt{36 + 9} \][/tex]
[tex]\[ IT = \sqrt{45} \][/tex]
Step 4: Calculate [tex]\( ET \)[/tex]:
[tex]\[ ET = \sqrt{(7 - 4)^2 + (5 - (-1))^2} \][/tex]
[tex]\[ ET = \sqrt{9 + 36} \][/tex]
[tex]\[ ET = \sqrt{45} \][/tex]
We notice that:
[tex]\[ KI = KE = \sqrt{17} \][/tex]
[tex]\[ IT = ET = \sqrt{45} \][/tex]
Since KITE has two pairs of adjacent sides that are equal ([tex]\( KI = KE \)[/tex] and [tex]\( IT = ET \)[/tex]), we can conclude that KITE is a kite.
Therefore, fill in the drop-down menus as follows:
1. [tex]\( IT = \sqrt{45} \)[/tex]
2. [tex]\( ET = \sqrt{45} \)[/tex]
3. Therefore, KITE is a kite because it has two pairs of adjacent sides of equal length, [tex]\( KI = KE \)[/tex] and [tex]\( IT = ET \)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.